Multi-strategy QoS-aware service selection and ranking model - Lei WU; Yu-long LIU; Shi-jun LIU (Tongxin xuebao)
As the increment of services with same function and different QoS in the internet,in order to select and rank the services that fulfill users’ functionality requirements and QoS requirements,a multi-strategy QoS-aware service ranking and selection approach is presented.Considering service performance,and service operation,maintenance costs,an extended Web service QoS model was developed.To determine how well a service satisfies users’and operators’ concerned QoS requirements,a set of functions is presented to normalize services’QoS on various QoS aspects with different metrics and scales,also to compute services satisfaction scores ,and to combine the users’satisfaction scores and the operators’scores together as an overall satisfaction scores based on certain strategy.A prototype system was built for service selection and ranking,and the model above was verified through an application case.